The Improvement of Humanity : Education and the French Revolution - Palmer, R. R. (Princeton, NJ : Princeton University Press, 2017)
This work examines education in both theory and practice during the Enlightenment and the French Revolution when educators aimed at nothing less than reforming humanity and creating a new society.Originally published in 1985.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- Contents -- Acknowledgments -- Preliminary Observations -- Chapter 1. Realities Before the Revolution -- Chapter 2. Nationalization -- Chapter 3. Politicization -- Chapter 4. Democratization: The Quest for Equality -- Chapter 5. Democratization: Building the Better World -- Chapter 6. Modernization: The Paths of Progress -- Chapter 7. Modernization: Collective Power -- Concluding Reflections -- Appendix -- Index
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 08. Jul 2019)
Keywords: Education -- France -- History -- 18th century; EDUCATION / History